Avaliação do potencial tóxico reprodutivo do extrato de Cordia ecalyculata Vell: em ratos Wistar - Santos, Mirian Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The use of extracts from Cordia ecalyculata is growing due to their potential to inhibit appetite. Its side effects on reproduction are unknown. Then , the study evaluated the reproductive toxic potential of different doses of the extract of C. ecalyculata in adult rats. The animals (n = 12/group) received distilled water (control group) and the hydroethano lic extract of C. ecalyculata in different doses (20, 100 and 400 mg / kg body weight). Treatments were administered orally (gavage), single dose/day for 60 consecutive days. At the end of treatment, the body weight of the animals that received the extract was similar to the control group, demonstrating the ineffectiveness of this herbal medicine in reducing body weight. The weight of the testes, seminal glands and prostate were no affected by treatments (p>0.05), but increased there was (p < 0.05) on the epididymis weight at a dose of 400 mg / kg of the extract. At all doses, the testes and epididymides showed histopathological changes, increased (p <0.05) the percentage of abnormal gametes in the epididymal tail and fertility of anim als was reduced (p<0.0 5). In conclusion that the extract of Cordia ecalyculata promoted re productive toxicity, but without dose - dependent effect

A utilização de extratos de Cordia ecalyculata está crescendo devido ao seu potencial em inibir o apetite. Seus efeitos colaterais na reprodução são desconhecidos. Então, o estudo avaliou o potencial tóxico reprodutivo de diferentes doses do extrato de C. ecalyculata e m ratos adultos. Os animais (n= 12 /grupo) receberam água destilada (grupo Controle) ou o extrato hidroetanólico de C. ecalyculata em diferentes concentrações de 1,5 ml (20, 100 e 400 mg/kg de peso corpóreo). Os tratamentos foram administrados por via oral (gavage), única dose/dia, durante 60 dias consecutivos. Ao final do tratamento, a massa corpórea dos animais que receberam o extrato foi similar ao grupo controle, demonstrando a ineficácia do fitoterápico na redução do peso corporal. O peso dos testículos, vesícul as seminais e próstata nã o foi afetados pelos tratamentos (p>0 ,05), mas houve aumento significativo no peso dos epidídimos na dose de 400 mg/kg do extrato. Em todas as doses, os testículos e epidídimos apresentaram alterações histopatológicas, houve aumento significativo no percen tual de gametas anormais na cauda do epidídimo e a taxa de fertilidade dos animais foi reduzida (p<0,05) . Concluiu - se que o extrato de Cordia ecalyculata promoveu toxicidade reprodutiva, porém com ausência de efeito dose - dependente
Keywords: Toxicologia; Embriologia; Rato como animal de laboratorio; Ratos Wistar; Toxicology